1987
DOI: 10.1037/h0079911
|View full text |Cite
|
Sign up to set email alerts
|

Methods of teaching introductory psychology: A Canadian survey.

Abstract: A survey about methods of teaching introductory psychology was sent to 50 Canadian universities. Responses were received from 33. Although 55% of the departments rely entirely on lectures for conveying information, a further 30% also rely on discussion/tutorial sessions. Twelve departments impose partial uniformity on instructors in multiple-section courses; ten impose none. Neither instructional format nor uniformity was related to enrolment. Most respondents rely heavily on objective questions for examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The weighting of MC items was especially heavy in larger classes, and in some courses MC items accounted for more than half of the course marks. Thus, MC items are not only widely used, but in many cases they are also a substantial determinant of students' course grades (Ross, Anderson, & Gaulton, 1987;Siegfried, Saunders, Stinar, & Zhang, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The weighting of MC items was especially heavy in larger classes, and in some courses MC items accounted for more than half of the course marks. Thus, MC items are not only widely used, but in many cases they are also a substantial determinant of students' course grades (Ross, Anderson, & Gaulton, 1987;Siegfried, Saunders, Stinar, & Zhang, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Surveys have indicated that in the vast majority of cases, introductorv psychology professors rely solely on objective tests (Ross, Anderson, 6 Gaulton, 1987). Use of undergraduate TAs provides the option of incorporating short-answer exams and papers into the class.…”
Section: Evaluative Feedbackmentioning
confidence: 99%